Molecular characterization, modeling and docking of CYP107CB2 from Bacillus lehensis G1, an alkaliphile. (June 2015) - Ang, Swi See; Salleh, Abu Bakar; Chor, Adam Leow Thean; Normi, Yahaya M.; Tejo, Bimo Ario; Rahman, Mohd Basyaruddin Abdul
Graphical abstract: Highlights: The putative gene CYP107CB2 from Bacillus lehensis G1 was classified into cytochrome P450 superfamily. CYP107CB2 is likely to interact with vitamin D3, 25-hydroxyvitamin D3 and 1α-hydroxyvitamin D3 as they were proximally located to the heme-iron. The findings provide important clues on substrates selectiveness to identify functional properties of new CYP107CB2. CYP107CB2 is a biologically active protein to produce 1α, 25-dihydroxyvitamin D3 from 1α-hydroxyvitamin D3 . Abstract: Cytochrome P450s are a superfamily of heme monooxygenases which catalyze a wide range of biochemical reactions. The reactions involve the introduction of an oxygen atom into an inactivated carbon of a compound which is essential to produce an intermediate of a hydroxylated product. The diversity of chemical reactions catalyzed by cytochrome P450s has led to their increased demand in numerous industrial and biotechnology applications. A recent study showed that a gene sequence encoding a CYP was found in the genome of Bacillus lehensis G1, and this gene shared structural similarity with the bacterial vitamin D hydroxylase (Vdh) from Pseudonocardia autotrophica . The objectives of present study was to mine, for a novel CYP from a new isolate B. lehensis G1 alkaliphile and determine the biological properties and functionalities of CYP in this bacterium. Our study employed the usage of computational methods to search for the novel CYP from CYP structural databases to identify the conserved pattern, functional domain and sequence properties of the uncharacterized CYP from B. lehensis G1. A computational homology model of the protein's structure was generated and a docking analysis was performed to provide useful structural knowledge on the enzyme's possible substrate and their interaction. Sequence analysis indicated that the newly identified CYP, termed CYP107CB2, contained the fingerprint heme binding sequence motif FxxGxxxCxG at position 336-345 as well as other highly conserved motifs characteristic of cytochrome P450 proteins. Using docking studies, we identified Ser-79, Leu-81, Val-231, Val-279, Val-383, Ala-232, Thr-236 and Thr-283 as important active site residues capable of stabilizing interactions with several potential substrates, including vitamin D3, 25-hydroxyvitamin D3 and 1α-hydroxyvitamin D3, in which all substrates docked proximally to the enzyme's heme center. Biochemical analysis indicated that CYP107CB2 is a biologically active protein to produce 1α, 25-dihydroxyvitamin D3 from 1α-hydroxyvitamin D3 . Based on these results, we conclude that the novel CYP107CB2 identified from B. lehensis G1 is a putative vitamin D hydroxylase which is possibly capable of catalyzing the bioconversion of parental vitamin D3 to calcitriol, or related metabolic products.